Continuing Caritas Journey—Reflections Upon a Shared Private Pilgrimage. (September 2014) - Watson, Jean
This manuscript is a continuing saga of an earlier walking pilgrimage ( El Camino in northern Spain): now a journey to Nepal, Bhutan, and Tibet, this time with others instead of alone. As I journeyed in close company with five others we experienced and expressed surprises about our selves and each other—our shared vulnerability, tolerance, and humility—uncovering lessons in living Caritas. As I trekked through these inner and outer adventures, Bhutan was discovered as a light of hope—a living metaphor of a people and a culture that hold and practice Caritas principles of loving—kindness, compassion, and equanimity for all sentient beings. Bhutan, a small country bordered by China and India, the only country in the world with a gross national happiness index and shared Caritas consciousness of oneness and connectedness of all, serves as a sacred path for humanity—a geographic Bodhisattva.